The components of the evaluation in science, technology and innovation: exploring the declarative dimension of STI policies for the case of Central America (1980-2020) - Viales-Hurtado, Ronny J.; Sáenz Leandro, Ronald; Garita Mondragón, Marco (Journal Studies of Public Policy, 2021)
This article means a first attempt to the evaluation approach present in the content of the scientific policies of Central America from a comparative perspective and alternative to the traditional scientometric analysis. Its general objective is to analyze the evaluation approach present in the scientific policies of Central America for the period 1980-2020. It has a double exploratory and descriptive scope, for which it starts from a methodological approach based on the content analysis of public policies, based on the evaluation classification in science and technology developed by Albornoz (2003), presenting the results of the proposal with comparative perspective. It concludes the importance of paying greater attention to the declarative dimension (content) of scientific policies in the sense of complementing and even improving the readings focused on performance indicators in the STI area. The results are taken as initial guidelines for the future generation of hypotheses and the dialogue with specialized literature on evaluation in scientific policies.